Releasing stimuli and aggression in crickets: octopamine promotes escalation and maintenance but not initiation - Rillich, Jan; Stevenson, Paul A. (Frontiers in Behavioral Neuroscience, 2015)
Biogenic amines have widespread effects on numerous behaviors, but their natural functions are often unclear. We investigated the role of octopamine (OA), the invertebrate analogue of noradrenaline, on initiation and maintenance of aggression in male crickets of different social status. The key-releasing stimulus for aggression is antennal fencing between males, a behavior occurring naturally on initial contact. We show that mechanical antennal stimulation (AS) alone is sufficient to initiate an aggressive response (mandible threat display). The efficacy of AS was augmented in winners of a previous fight, but unaffected in losers. The efficacy of AS was not, however, influenced by OA receptor (OAR) agonists or antagonists, regardless of social status. Additional experiments indicate that the efficacy of AS is also not influenced by dopamine (DA) or serotonin (5HT). In addition to initiating an aggressive response, prior AS enhanced aggression exhibited in subsequent fights, whereby AS with a male antenna was now necessary, indicating a role for male contact pheromones. This priming effect of male-AS on subsequent aggression was dependent on OA since it was blocked by OAR-antagonists, and enhanced by OAR-agonists. Together our data reveal that neither OA, DA nor 5HT are required for initiating aggression in crickets, nor do these amines influence the efficacy of the natural releasing stimulus to initiate aggression. OA’s natural function is restricted to promoting escalation and maintenance of aggression once initiated, and this can be invoked by numerous experiences, including prior contact with a male antenna as shown here.